The potential of bio certification to strengthen the market position of food producers - Yevhen Kononets; Horst Treiblmaier (Modern Supply Chain Research and Applications, 2021)
Purpose: The purpose of the paper is to critically evaluate the applicability of bio certification in farmers' activity to reduce unfair trading practices in the food supply chain. The secondary purposes are describing the economic reasons of using bio certification and perspectives of using web trading platforms among food producers. Design/methodology/approach: Data collection included face-to-face interviews with 15 Austrian and German farmers who operate on bio food markets as well as a quantitative survey regarding their assessment of unfair trading practices. This study presents both quantitative and qualitative analyses. Findings: Bio certification is more likely unable to eliminate or mitigate unfair trading practices in the food supply chain, however bio certification is able to increase efficiency of farmers together with other web tools. Originality/value: The study is the first to empirically investigate the applicability of bio certifications, its advantages and impact on unfair trading practices in the food supply chain. It focuses on small and medium-sized food producers and farmers. The research also reveals the perspectives of using web trading platforms in farming activity.
Keywords: 650; Unfair trading practices; Food supply chain; Bio certification; Fairtrade; Fair trade; Trading platforms; Food producers; Survey